An Ecological Study of Red Junglefowl (Gallus Gallus Spadiceus) in Agriculture Areas - Arshad, Muhammad Irshad (1999)
A two-year study on the ecology of Red Junglefowl (Gallus gallus spadiceus) was conducted in five selected agriculture areas in the state of Selangor. In the first year (from August 1995 to July 1996), the study was done in three areas viz. rubber plantation, 22-year old oil palm plantation and orchard area at Universiti Putra Malaysia. In the second year (from August 1996 to July 1997), another two areas viz. 4-year and 8-year old oil palm plantations at Sungai Sedu Estate, Selangor were selected. Red Junglefowl density was estimated by transect survey. The densities in 4-year, 8-year and 22-year old oil palm plantations, orchard area and rubber plantation were 84.221km2, 27.801km2, 21,431km2, 15.661km2 and 6.061km2 respectively. Male and female ratio was 1:1.25. The abundance of arthropods did not seem to affect the density of Red Junglefowl. Four Red Junglefowls were radio tagged in oil palm plantation to observe the home range size and movement. The Red Junglefowl tracking was made by triangulation technique. The daily and monthly home range of male was larger than that of female and also the total daily movement of male was larger than female. The maximum home range size of male and female were 312.50 ha and 49.07 ha respectively. The study on breeding ecology showed that generally, one male was observed with a single female and rarely with two to four females. A total of 95 nests were observed during the entire period of study. The Red Junglefowl breeds throughout the year with a peak in December 1996. The mean clutch size was 4.08 eggs. The incubation period in captivity was approximately 19.5 days. The hatching percentage of eggs in nature was 99% whereas, the rate of desertion of nests was 80%. The predators of eggs and chicks in the agriculture areas were stray dogs, snakes, monitor lizards and big carnivorous birds. Foraging ecology of Red Junglefowls shows that they fed in open areas early in the morning and evening and the rest of the day they fed under trees. They are opportunistic feeders and ate a variety of animal and plant components. The male Red Junglefowl consumed oil palm fruit more than the female whereas the female consumed more animal materials than the male. Roosting ecology shows that the Red Junglefowl preferred horizontal branch/frond for roosting at night and changed branches and trees from time to time. The roosting height varied between 5 to 9 m in orchard area and 4 to 12 m in oil palm plantations. Red Junglefowl departed about 3 minutes earlier before sunrise and roosted about 6 minutes before sunset. The male Red Junglefowl crowed for finding or attracting a mate and for announcing or protecting its territory. The crowing frequency was high when a nonterritorial male entered the territory of a territorial male. Alarm calls were given by both sexes when there was a danger especially when predators were nearby.